1996
DOI: 10.1002/macp.1996.021971022
|View full text |Cite
|
Sign up to set email alerts
|

Novel sulfur‐containing ferrocene polymers

Abstract: Ferrocene-containing polymers were synthesized via addition reaction of 1 , 1'-dimercaptoferrocene (1) and l,l'-bis(2-mercaptoethyl)ferrocene (2) to various diolefinic monomers such as dimethacrylates, divinyl ethers, divinyl sulfones and others. The dithiol 1 was also used as a monomer in condensation reactions with bifunctional acid chlorides. The polymerization of propylene sulfide in the presence of 1 as a bifunctional initiator was found to lead to polymers with a single central ferrocene unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…As a side‐result of these studies, this polymerisation mechanism revealed a noticeable robustness: for example, it is not sensitive to the presence of protic groups, such as alcohols, possibly being present in the monomer structure;110 indeed, the episulfide anionic polymerisation can even be performed in an aqueous environment, provided an the pH is appropriately high to avoid protonation of thiolates 111. Finally, functional groups that are not sensitive to thiols or mildly basic conditions can be incorporated on the polysulfide chains by the use of appropriate end‐capping agents or iniators; in this way, metallo‐organic compounds,112 fluorescent tags and post‐polymerisable groups113 have been introduced as terminal groups on poly(propylene sulfide).…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…As a side‐result of these studies, this polymerisation mechanism revealed a noticeable robustness: for example, it is not sensitive to the presence of protic groups, such as alcohols, possibly being present in the monomer structure;110 indeed, the episulfide anionic polymerisation can even be performed in an aqueous environment, provided an the pH is appropriately high to avoid protonation of thiolates 111. Finally, functional groups that are not sensitive to thiols or mildly basic conditions can be incorporated on the polysulfide chains by the use of appropriate end‐capping agents or iniators; in this way, metallo‐organic compounds,112 fluorescent tags and post‐polymerisable groups113 have been introduced as terminal groups on poly(propylene sulfide).…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…Ferrocene remains after about 55 years since its discovery a molecule of intrigue and continued interest. The sustained interest in ferrocene is in part due to the rich chemistry of iron(II) center and the variety of synthetic methods available for functionalizing the cyclopentadienyl ligands [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[114] Reaction of 1,1 0 -dimercaptoferrocene or 1,1 0 -bis(2-mercaptoethyl)ferrocene with various diolefins allowed for the isolation of new classes of polymetallocenes. Scheme 28 shows the reaction of …”
Section: Polymerization Of Olefin-functionalized Metallocenesmentioning
confidence: 99%
“…The reaction of organic acid chlorides with 1,1 0 -dimercaptoferrocene was reported by Nuyken and coworkers. [114] In 2001, Osakada and coworkers reported the rhodiumcatalyzed polymerization of 1,1 0 -dimercaptoferrocene with diarylsilanes as shown in Scheme 33. [125] These reactions yielded a mixture of polymers with M n values ranging from 2 700 to 4 600 and a ferrocenophane.…”
Section: Polycondensation Of Metallocenesmentioning
confidence: 99%
See 1 more Smart Citation